Poly(methyl methacrylate) and glycidyl-functionalized poly(methyl methacrylate) nano-size latex particles via differential microemulsion polymerization - Chaiwat Norakankorn (Chulalongkorn University, 2013)
Thesis (Ph.D)--Chulalongkorn University, 2007